Sexuality education and religion: From dialogue to conversation. Issue 5 (18th November 2022) - Henry, Seán; Heyes, Joshua M.
Abstract: The relationship between sexuality education and religion is often framed antagonistically, especially when it comes to tensions between the teaching of sexuality education and the priorities of some religious communities. In this paper, we argue that this antagonism can be structured as much by the prevalent forms of engagement that display it (dialogue and debate), as it is by the antagonism between contrasting ethical systems.  While we acknowledge the importance of debate and dialogue in the public sphere, we contend that appeals to these discursive forms in schools and classrooms can limit possibilities for rethinking engagements across sexuality education and religion. This is because of the tendency within certain manifestations of dialogue (for example, dialogical models connected to liberal political projects) to err on the side of predictability, rationality and abstraction. To address some of these limits, we draw on the recent turn to conversation in educational thinking. We think through the significance of conversation in offering a mode of engagement for students, teachers and school communities that is conditioned by the dispossession of the self and is attuned to the unpredictable, affective and contextual landscapes of shared encounters. We conclude with some thoughts on the practical implications of conversation for rethinking the role of the sexuality education teacher, practices of parental consultation and processes of policy enactment in schools.